The impact of alkyl polyglycoside surfactant on oil yields and its potential effect on the biogenic souring during enhanced oil recovery (EOR). (15th November 2020) - do Vale, Tatiana Oliveira; de Magalhães, Roberta Santoro; de Almeida, Paulo Fernando; Matos, Josilene Borges Torres Lima; Chinalia, Fábio Alexandre
Graphical abstract: Highlights: Lauryl glucoside is efficient at 2% (w/v) during oil recovery. SRBs can grow on surfactant or oil as sole carbon sources. Surfactant concentrations cause distinct impact on biogenic souring. Low surfactant concentrations increase biogenic souring. High surfactant concentrations inhibit biogenic souring. Abstract: The aim of this work is to quantify the effect of using alkyl polyglycoside (APG) surfactant as the main agent for oil recovery and to quantify its potential impact on biogenic souring. Sand-pack column replicates were subjected to two surfactant concentration injection events both in the presence and absence of oil. The activity of sulphate-reducing bacteria (SRB) was tested using the distinct resultant produced waters (PWs) or with surfactant solutions as the additional carbon source. The results suggested that a surfactant concentration of 2% (w/v) can recover 7.7 fold more oil than 0.1% (w/v). The PWs SRB-activity testing identified that surfactant concentrations below 1% (w/v) can significatively increase microbial activity (256μgSO4 /L/h) - which enhances biogenic souring. PWs with higher surfactant concentrations inhibited SRB-activity in the presence of oil. SRB-microbes can utilize surfactant as the sole carbon source (concentrations below 2% w/v). Thus, the mixture of surfactant and oil increased or decreased SRB-activity depending on their concentration (low/high, respectively). Surfactant can not only assist in enhancing biogenic souring but, at a higher concentration, may control it without the need of employing significant amounts of biocide.